2011
DOI: 10.1080/1612197x.2011.563128
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of the two-factor schematization of relation meaning and emotions among professional rugby union players

Abstract: The aim of this paper was to explore Lazarus's two-factor schematization of losses and gains and the emotions generated in response to loss (threat and harm) and gain (challenge and benefit) relational meanings. Participants were 10 professional rugby union players aged between 24 and 35 years (M age ¼ 26.8 years, SD ¼ 5.92). The results revealed that at different times, the same stressor had different relational meanings. For instance, opponent, coach, playing an important match, and injury stressors were app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 26 publications
6
31
0
2
Order By: Relevance
“…From an applied perspective, these findings have important implications. Teaching athletes to generate positive appraisals may lead to more positive emotions being experienced (see Nicholls et al, 2011), which may result in more task-oriented coping strategies being deployed. This may be beneficial to performance given that taskoriented coping was found associated with better performances among golfers (Gaudreau, Nicholls, & Levy, 2010).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…From an applied perspective, these findings have important implications. Teaching athletes to generate positive appraisals may lead to more positive emotions being experienced (see Nicholls et al, 2011), which may result in more task-oriented coping strategies being deployed. This may be beneficial to performance given that taskoriented coping was found associated with better performances among golfers (Gaudreau, Nicholls, & Levy, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…With a sample of 11 professional rugby union players, Nicholls et al (2011) found that gain (i.e., challenge and benefit) appraisals were associated with pleasant emotions, whereas loss (i.e., harm/loss and threat) appraisals were associated with unpleasant emotions. This finding was also replicated with a sample of 557 athletes.…”
Section: Stress Appraisals and Emotionsmentioning
confidence: 97%
“…For example, the perceptions of stressors could result in certain verbalisations being more evident in earlier stages. The perceived importance of the event may have contributed to these findings (Nicholls et al, 2011); given that this was a real-life TT event, it could be suggested that this was perceived as more important than other training events or a laboratory-based study. The initial verbalisations could be the result of a stress response, however as the TT progresses, participants may employ specific coping strategies and develop perceptions of control over the event (Billat et al, 2001).…”
Section: Insert Table 3 Here Discussionmentioning
confidence: 99%
“…Apesar de parecer óbvia esta necessidade, a verdade é que conseguir integrar todas as dimensões envolvidas nesta relação num único estudo é uma tarefa difícil e complexa. É, por isso, que quando analisamos grande parte dos estudos efetuados sobre este tópico no domínio desportivo e que têm por base a proposta transacional de Lazarus, constatamos que tendem a estudar este fenómeno de um modo parcelar, ora focando-se nos fatores de stress (Campbell & Jones, 2002;Fletcher, & Hanton, 2003;McKay, Niven, Lavallee, & White, 2008;Noblet & Gifford, 2002), nos processos de avaliação cognitiva (Balk, Adriaanse, de Ridder, & Evers, 2013;Nicholls, 2007;Nicholls, Polman, Morley, & Taylor, 2009) ou nas emoções resultantes (Nicholls, Levy, Jones, Rengamani, & Polman, 2011;Rathschlag & Memmert, 2015), existindo menos estudos centrados na relação interativa entre todos eles (Nicholls, Perry, & Calmeiro, 2014).…”
Section: Nota De Investigação | Research Noteunclassified
“…Este aspeto é tanto mais relevante quando pensamos no desporto, uma vez que se trata de um contexto potencialmente promotor de elevada pressão e stress nos atletas (Balk et al, 2013;Nicholls et al, 2011). Por isso, a questão que se coloca é como é que as abordagens transacional e interativa expostas neste trabalho podem ajudar o psicólogo do desporto a intervir nestes casos.…”
Section: Implicações Para a Intervenção E Investigaçãounclassified